Rancang Bangun Aplikasi Manajemen Kos Menggunakan Framework Flutter - Putrawanto, Daris Irfan; Wibowo, Nur Cahyo; Permatasari, Reisa (JATISI, 2024)
Indekos or in general language kos-kosan is a business that provides rooms for rent for a certain period of time in accordance with the agreement between the boarding room occupant and the boarding house owner. Several problems arise from living in a boarding house, such as not getting to know each other, there is no platform for borrowing boarding facilities, recording boarding house payments, and submitting boarding house complaints. Therefore, a boarding house management application is needed to be able to help boarding house owners and managers in managing a boarding house and assist boarding house residents in occupying a boarding house. This research uses waterfall methodology. Designed on a mobile platform using the flutter framework and dart programming language. Firebase was chosen as the database for the data storage needs of this application. Black box test was chosen as a testing method for direct users. The results obtained were that all tests were carried out successfully. From the creation of this boarding house management application, it is hoped that it will be able to answer user needs that are directly related to boarding houses.